Уточненная математическая модель электрического источника постоянного геомагнитного поля - Баранов, Михаил Иванович (НТУ "ХПИ", 2012)
Приведена уточненная модель внутреннего электрического источника биполярного постоянного магнитного поля (ПМП) Земли. Данная модель источника геомагнитного поля построена на круговых избыточных электронных токах полужидкой мантии Земли. На основе предложенной модели выполнена численная оценка ПМП в области магнитных полюсов и у экватора Земли. Произведено сравнение полученных расчетных и известных опытных данных для индукции геомагнитного поля.

A refined model of the internal electric source of the Earth’s bipolar permanent magnetic field (PMF) is presented. This model of the geomagnetic field source is based on circular ex-cess electron currents of the Earth’s semisolid mantle. With the model introduced, numerical evaluation of the PMF in the area of the magnetic poles and at the equator of the Earth is made. For induction of the geomagnetic field, calculated data obtained are compared with available experimental data.
A refined mathematical model of the electric source of the permanent geomagnetic field
Keywords: биполярность; мантия полужидкая; ток электронный; ток круговой; оценка; полюс магнитный; экватор; Земля; планета; mathematical model; permanent geomagnetic field; internal electric source; numeral evaluation